Pengaruh Media Film Animasi Terhadap Penguasaan Kosakata Bahasa Inggris Siswa Sekolah Dasar - Silva Lisnawaty Hidayat; Arsyi Rizqia Amalia; Dyah Lyesmaya (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
English is a universal language that needs to be mastered in order to be able to compete with the development of this world. Therefore, learning English needs to be given at elementary school age. In language learning the most basic thing is vocabulary. Mastery of vocabulary also determines one's language ability. However, in learning in elementary schools, media assistance is needed to help students understand the material. Technological developments are increasingly rapid, with that learning media that can be used are increasingly diverse, one of which is animated films. This study aims to determine the effect of animated film media on vocabulary mastery of fifth grade students in elementary school. From the results of data analysis, it was concluded that: 1) it was found that there was an effect on students' vocabulary from animated film media with a significant value of 0.00 < 0.05, those Ho was rejected and H1 was accepted. 2) the average difference in student learning outcomes with a value of 42.18 in the control class and 45.18 in the experimental class. Based on these findings, it can be concluded that the animated film media has a significant influence on the vocabulary mastery of elementary school students.